2022
DOI: 10.3390/polym15010172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fly Ash and Hexadecyltrimethoxysilane on the Compressive Properties and Water Resistance of Magnesium Oxychloride Cement

Abstract: The application of magnesium oxychloride cement (MOC) is promising, but its poor water resistance seriously hinders its development and application. In this paper, we describe a new type of MOC with excellent water resistance, prepared using fly ash and hexadecyltrimethoxysilane (HDTMS). SEM, XRD, FTIR, TG/DSC, and other microscopic-scale studies were conducted to investigate the mechanism underlying the water-resistance enhancement of the new MOC. It was found that adding 20% fly ash and 3% HDTMS can strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…FA is a byproduct of the coal industry, and it was discovered that using FA considerably increased the water resistance of MOC. Figure 2 depicts the water resistance coefficients of FA-modified MOC composites as reported in previous studies [66,67]. Previous research has shown that incorporating 30% FA into MOC mortar (14 d air-cured) resulted in 80% compressive strength retention with respect to the initial value after 28 d of immersion in water [22,68].…”
Section: Influence Of Scms On the Properties Of Moc 41 Effect Of Fa O...mentioning
confidence: 74%
See 1 more Smart Citation
“…FA is a byproduct of the coal industry, and it was discovered that using FA considerably increased the water resistance of MOC. Figure 2 depicts the water resistance coefficients of FA-modified MOC composites as reported in previous studies [66,67]. Previous research has shown that incorporating 30% FA into MOC mortar (14 d air-cured) resulted in 80% compressive strength retention with respect to the initial value after 28 d of immersion in water [22,68].…”
Section: Influence Of Scms On the Properties Of Moc 41 Effect Of Fa O...mentioning
confidence: 74%
“…Strength retention coefficient of FA-modified MOC after water immersion. (Note-CM: control mix, HDTMS: hexadecyltrimethoxysilane, and SF: silica fume)[19,20,22,66,68].…”
mentioning
confidence: 99%
“…The dense microstructure of the MOC was primarily attributed to the filling effect of fine fly ash particles and the formation of Mg-Cl-Si-H gel. This increases the water resistance of the MOC-stabilized crushed stone to a certain extent 8,11,13,36,38 . However, when the fly ash content surpasses a certain proportion, the excessive fly ash increases the proportion of harmful pores, adversely affecting the water resistance.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Solidification/stabilization (S/S) methods can prevent harmful chemicals from being released into the environment though chemical or mechanical binding using curing agents [6,[58][59][60]. Magnesium oxychloride cement (MOC), known as Sorel cement, comprises MgO and MgCl 2 ; it is typically used as a curing agent for S/S of solid waste, because of its good engineering and mechanical properties, fast curing, air hardening, good resistance to abrasion and fire, and so on [61][62][63][64][65][66][67]. MgO and MgCl 2 react with water to form MgO-MgCl 2 -H 2 O systems such as Mg(OH) 2 •MgCl 2 •8H 2 O (phase 3) and 5 Mg(OH) 2 •MgCl 2 •8H 2 O (phase 5), which are the main substances to form strength of MOC-solid waste in the solidifying process [64,[67][68][69][70][71][72][73][74][75].…”
Section: Introductionmentioning
confidence: 99%